Analysis of Delta In-Out of natural gas distribution networks. (April 2022) - Ficco, G.; Frattolillo, A.; Zuena, F.; Dell'Isola, M.
Abstract: In recent years, the estimation of Unaccounted for Gas in natural gas networks has been a very debated topic in the scientific literature and within regulatory authorities. In fact, this issue has broad implications since it can affect the cost of supplying gas, the safety of the service and the environmental impact. Unfortunately, although this issue has been widely focused in transmission networks, large and generalized literature studies for the distribution sector are still lacking. In this paper, a theoretical study of the causes of Delta In-Out in natural gas distribution networks, of the related applied analysis methodologies have been presented, together with an in-depth analysis of the Delta In-Out in Italian distribution networks. To this aim, Delta In-Out of 2904 natural gas distribution networks in Italy in the period 2013–2017 have been analyzed aimed at focusing the relevant aspects of the phenomenon and at identifying appropriate reduction strategies. A national average value of Delta In-Out approximately equal to +1% was found, whereas the standard deviation significantly varies depending on the size of the network (i.e. from about 2% for large networks to 10% in small networks) and on the climatic zone (i.e. from about 3% for networks in center-north Italy to 11% in the southern ones). Highlights: Balancing of natural gas networks is a crucial tool for management purposes. Delta In-Out is a crucial balancing issue in both transmission and distribution networks. Delta in-out causes have been analyzed and discussed. Delta In-Out trends in the Italian distribution networks over a five-year time period are presented and discussed.